2015
DOI: 10.1111/nan.12252
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal DNA damage response‐associated dysregulation of signalling pathways and cholesterol metabolism at the earliest stages of Alzheimer‐type pathology

Abstract: AimsOxidative damage and an associated DNA damage response (DDR) are evident in mild cognitive impairment and early Alzheimer's disease, suggesting that neuronal dysfunction resulting from oxidative DNA damage may account for some of the cognitive impairment not fully explained by Alzheimer‐type pathology.MethodsFrontal cortex (Braak stage 0–II) was obtained from the Medical Research Council's Cognitive Function and Ageing Study cohort. Neurones were isolated from eight cases (four high and four low DDR) by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…It has been suggested that oxidative damage is a very early event, which can lead to neuronal dysfunction and AD independently or in conjunction with other factors [79]. Silva et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that oxidative damage is a very early event, which can lead to neuronal dysfunction and AD independently or in conjunction with other factors [79]. Silva et al .…”
Section: Discussionmentioning
confidence: 99%
“…Data-mining of mRNA expression in AD patients The expression level of the COX-related genes in AD was retrieved from the AlzData database (www.alzdata.org) [73], in which we have integrated and normalized the original microarray data of 684 AD brain tissues and 562 control tissues from Gene Expression Omnibus (GEO: http://www.ncbi.nlm.nih.gov/sites/GDSbrowser) [19,[74][75][76][77][78][79][80][81][82][83][84][85][86]. We used the stage I data as defined in Xu et al [73] that contains expression data of 269 AD brain tissues and 271 control brain tissues from four brain regions (entorhinal cortex, hippocampus, temporal cortex, and frontal cortex) to investigate the alteration of mRNA levels of the COX-related genes in AD, by using a two-tailed Student's t-test with the GraphPad Prism software (GraphPad Software, La Jolla, CA, USA).…”
Section: Subjectsmentioning
confidence: 99%
“…Seven expression datasets of frontal cortex from 104 AD patients and 128 controls were retrieved from the GEO: GSE48350 [80], GSE66333 [81], GSE53890 [77], GSE5281 [19], GSE36980 [76], GSE12685 [86], and GSE15222 [85] Entorhinal cortex CN AD The mRNA levels of the COX-related genes were significantly decreased in entorhinal cortex and hippocampus tissues of AD patients. a-j The mRNA expression data of the COX-related genes in entorhinal cortex and hippocampus tissues were retrieved from the NCBI Gene Expression Omnibus (GEO, https://www.ncbi.nlm.nih.gov/geo) and were normalized and analyzed in the AlzData database (www.alzdata.org) [73].…”
Section: Genetic Variants In the Cox-related Genes Were Associated Wimentioning
confidence: 99%
“…Similarly, although many studies show a decrease of NMNAT2 transcript postmortem in patients with neurodegenerative diseases, there is also evidence of increased levels at the early stages of disease. For example, in mild cognitive impairment and early stages of AD, NMNAT2 mRNA levels are higher in the frontal cortex of patients exhibiting high levels of oxidative stress-induced neuronal DNA damage, compared to those with lower levels of DNA damage [45]; at this stage the nervous system is mounting a stress response as HSP90 is also upregulated in patient brains with high oxidative damage. In a genome-wide gene-expression study of another mouse model of FTDP-17, Nmnat2 transcript is significantly upregulated in the hippocampus during early disease progression, but is downregulated at end stages of disease when neurofibrillary tangle burden is heavy [46].…”
Section: Regulation Of Nmnat During Stress and Diseasementioning
confidence: 99%